Zero separation policy in small but stable neonates weighing 1500-2000 grams at birth: a single center study in New Delhi, India - Rohit Anand; Srishti Goel; Sugandha Saxena; Bhawna Dubey; Gunjana Kumar; Sushma Nangia (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Small but stable low birth weight (LBW) neonates have needs similar to babies of normal weight with the need for extra support with feeding and temperature maintenance. Most health facilities admit such infants in the neonatal unit leading to the separation of the mother and baby. This separation exposes the infant to a potentially contaminated environment of the Neonatal intensive care unit (NICU) which is hazardous for stable infants (Invasive interventions, Intravenous alimentation, Infections) and also hampers the establishment of breastfeeding. This study evaluated short-term outcomes of stable neonates weighing 1500-2000 grams at birth cared for in the mother-baby unit in the same room. as their mothers as per the 'Zero-separation Policy'. # Methods Neonates born vaginally with a birth weight of 1500-2000 grams with stable vitals were moved with their mothers to a 12-bed ''mother-baby unit (MBU)". Mothers were counseled regarding breastfeeding (BF), Kangaroo mother care (KMC), maintenance of general hygiene, and identification of danger signs. Infants developing moderate to severe hypothermia, hypoglycemia, feed intolerance (FI), jaundice nearing exchange transfusion range, respiratory difficulty, sepsis, seizures, or apnea, were moved to a neonatal unit for further management. # Results Over 3 years, 489 neonates with a mean (± SD) birth weight of 1738 ± 102 grams and median gestation of 34 weeks (range: 32-41 weeks) were cared for with their mothers at the MBU. Seventy percent of infants exclusively received their mother's own milk on day 1, which increased to more than 95% from day 4 onwards. Similarly, two-thirds of the mothers provided KMC for at least 5-8 hours on day 1, increasing to 85% by day 5. Neonatal hyperbilirubinemia requiring treatment was the most common morbidity (28.8%), most of which was managed at the bedside, followed by hypoglycemia (4.7%). Only 8% of neonates (n= 39/489) required transfer to the neonatal unit, mostly for hypoglycemia and hyperbilirubinemia. No baby developed hypothermia, apnea, FI, seizures, or hemodynamic instability. Successful discharge to home was accomplished in all neonates with no mortality. # Conclusions Zero-separation policy is feasible in clinically stable low-weight or small neonates (of 1500-2000 grams) who can be nurtured with their mothers right from birth, ensuring timely feeding, KMC, and good hygienic practices.